Practice guidelines for thyroid disorders (Malaysian Endocrine and Metabolic Society, 2000)
Thyroid disorders together with diabetes mellitus are the most common and prevalent endocrine and metabolic diseases in this country. Thus, having completed a guideline on the management of type 2 diabetes mellitus, the Malaysian Endocrine and Metabolic Society (MEMS) took the task to prepare the Malaysian Consensus for Practice Guidelines for Thyroid Disorders. These guidelines hopefully will be use to assist practising doctors in the management of patients with thyroid disorder